2008
DOI: 10.1007/s11430-008-0059-7
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Cu-Ni-Zn-Sn-Fe intermetallic compounds and S-bearing alloys in the Zhaishang gold deposit, southern Gansu Province and its geological significance

Abstract: Examination of ores by optical microscope and EPMA from the Zhaishang gold deposit, southernGansu Province, has revealed an abundance of rare minerals. These include native metals, Cu-Ni-Zn-Sn-Fe polymetallic compounds and S-bearing alloys of Ni, Fe, Zn, Cu and Sn, occurring as native nickel, Zn-Cu alloy, Ni-Zn-Cu alloy, Sn-Zn-Ni-Cu alloy, Zn-Cu-Ni alloy, Zn-Fe-Cu-Sn-Ni alloy, Fe-Ni-S alloy, Sn-Fe-Ni-S alloy, Fe-Zn-Cu-Ni-S alloy, Zn-Ni-Cu-Fe-S alloy and others. Compared with the Zn-Cu alloy minerals discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…At present, Cu–Zn intermetallics which have been reported in China include CuZn 2 (Danbaite; Yue et al ., ), CuZn (Zhanghengite; Wang, ), Cu 3 Zn (Li et al ., ), Cu 2 Zn (Lang et al ., ; Shuai et al ., ; Luo and Wang, ; Zhang et al ., ) and Cu 7 Zn 4 (Xiao et al ., ; Sun et al ., ). At the Zhaishang Au deposit (Gansu Province, PRC), a large number of other Cu–Zn intermetallics have also been reported, including α phase Zn–Cu intermetallic compound (Cu 0.88 Zn 0.11 Fe 0.01 ), α + β phase Zn–Cu intermetallic compound (Cu 0.58 Zn 0.35 Fe 0.04 Ni 0.03 ), Ni–Zn–Cu intermetallic compound (Cu 0.54 Zn 0.35 Ni 0.08 Fe 0.03 ), Zn–Ni–Cu intermetallic compound (Cu 0.42 Ni 0.30 Zn 0.26 Fe 0.02 ) and Sn–Zn–Ni–Cu intermetallic compound (Cu 0.42 Ni 0.26 Zn 0.23 Sn 0.07 Fe 0.02 ) (Liu et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…At present, Cu–Zn intermetallics which have been reported in China include CuZn 2 (Danbaite; Yue et al ., ), CuZn (Zhanghengite; Wang, ), Cu 3 Zn (Li et al ., ), Cu 2 Zn (Lang et al ., ; Shuai et al ., ; Luo and Wang, ; Zhang et al ., ) and Cu 7 Zn 4 (Xiao et al ., ; Sun et al ., ). At the Zhaishang Au deposit (Gansu Province, PRC), a large number of other Cu–Zn intermetallics have also been reported, including α phase Zn–Cu intermetallic compound (Cu 0.88 Zn 0.11 Fe 0.01 ), α + β phase Zn–Cu intermetallic compound (Cu 0.58 Zn 0.35 Fe 0.04 Ni 0.03 ), Ni–Zn–Cu intermetallic compound (Cu 0.54 Zn 0.35 Ni 0.08 Fe 0.03 ), Zn–Ni–Cu intermetallic compound (Cu 0.42 Ni 0.30 Zn 0.26 Fe 0.02 ) and Sn–Zn–Ni–Cu intermetallic compound (Cu 0.42 Ni 0.26 Zn 0.23 Sn 0.07 Fe 0.02 ) (Liu et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Ever since the first discovery of Cu-Zn intermetallics in lunar rock (Apollo-11) (Agrell et al, 1970), various natural Cu-Zn intermetallic compounds have been described in aerolite, granite, ophiolite, kimberlite, lamproite, gabbrodolerite, quartz diorite, volcanic tuff and ore deposits of diamonds, porphyry copper, Cu-Ni sulphides, REE, gold, the oxidized zone of sulphides and residual talus. As examples, large quantities of Cu-Zn intermetallics are hosted by ophiolite in the Far-east Koryak Plateau (Rudashevsky et al, 1987(Rudashevsky et al, , 1988, the quartz gold deposit of Sukhol Log in Russia (Distler et al, 2004), kimberlite, lamproite, compound (Cu 0.42 Ni 0.30 Zn 0.26 Fe 0.02 ) and Sn-Zn-Ni-Cu intermetallic compound (Cu 0.42 Ni 0.26 Zn 0.23 Sn 0.07 Fe 0.02 ) (Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Liu et al showed that TiO 2 could increase the highest occupied molecular orbital space size of noble metals and decrease the adsorption of atomic oxygen on the catalyst compared with catalysts supported on carbon. 21 Zhao et al employed TiO 2 nanotubes as catalyst supporst for LOBs, and their huge specific surface area could provide abundant active sites for Li 2 O 2 precipitation. 22 In addition, the channels in the nanotubes were beneficial to oxygen transport, which improved the specific capacity, rate performance, and cyclability of LOBs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various catalysts, TiO 2 is an attractive catalyst support because it is stable, environmentally friendly, and biocompatible. , Liu et al showed that TiO 2 could increase the highest occupied molecular orbital space size of noble metals and decrease the adsorption of atomic oxygen on the catalyst compared with catalysts supported on carbon . Zhao et al employed TiO 2 nanotubes as catalyst supporst for LOBs, and their huge specific surface area could provide abundant active sites for Li 2 O 2 precipitation .…”
Section: Introductionmentioning
confidence: 99%